Study of the Combustion Characteristics of a Compression Ignition Engine Fueled with a Biogas–Hydrogen Mixture and Biodiesel - Alfredas Rimkus; Justas Žaglinskis (Journal of Marine Science and Engineering)
Increasing the use of renewable energy sources is essential to reduce the use of fossil fuels in internal combustion engines and to reduce greenhouse gas emissions. An experimental and numerical simulation study of the combustion process of a compression ignition engine was carried out by replacing fossil diesel with a dual fuel produced from renewable energy sources. In conventional dual-fuel applications, fossil diesel is used to initiate the combustion of natural gas or petroleum gas. In the present study, fossil diesel was replaced with advanced biodiesel – hydrotreated vegetable oil, and natural gas was replaced with biogas. In the experimental study, a gas mixture of 60% natural gas (by volume) and 40% carbon dioxide (by volume) was used to replicate the biogas while maintaining a 40%, 60%, and 80% gas energy share in the fuel. It was observed that using fossil diesel and biogas in the dual-fuel engine significantly slowed down the combustion process, which normally resulted in poorer energy performance. One way to compensate for the lack of energy (due to the presence of carbon dioxide) in the cylinder is to use a gas such as hydrogen, which has a high energy content. To analyze the effect of hydrogen on the dual-fuel combustion process, hydrogen gas was added to the replicated biogas at 10%, 20%, and 30% of the natural gas volume, maintaining the biogas at a (natural gas + hydrogen)-to-carbon dioxide volume ratio of 60%/40% and the expected gas energy share. The combustion process analysis, which was conducted using the AVL BOOST software (Austria), determined the heat release rate, temperature, and cylinder pressure rise in the dual-fuel operation with different renewable fuels and compared the results with those of fossil diesel. It was found that when the engine was operated at medium load and with the flammability of the biogas approaching the limit, the addition of hydrogen significantly improved the combustion characteristics of the dual-fuel engine.